PEMBUATAN SUSU FERMENTASI PROBIOTIK MENGGUNAKAN Lactobacillus casei Subsp. casei R-68 DENGAN PENAMBAHAN EKSTRAK BUAH NAGA MERAH - RIYA ANDILA; USMAN PATO (Universitas Riau, 2018)
Probiotic fermented milk by Lactobacillus casei subsp. casei R-68 with skim milk and red dragon fruit extractas a raw material was expected to produce probiotic fermented milk with more completed nutriotional valueand health benefits. The purpose of this study was to determine the best percentage of red dragon fruit extracton the quality of fermented milk. This study used a Completely Randomized Design Experiment with fourtreatmentsnamely BN1 = 2% red dragon fruit extract, BN2 = 4% red dragon fruit extract, BN3 = 6% reddragon fruit extract, BN4 = 8% red dragon fruit extract and three replications. Data were analyzed usingANOVA, followed by DNMRT at 5% level. The results show that the concentration of red dragon fruit extractsignificantly (P <0.05) influenced the pH value, total lactic acid, total lactic acid bacteria, the sensory testby descriptive and hedonic of colour and hedonic of taste. but did not significantly affect (P> 0.05) protein,solid total, the sensory test by descriptive and hedonic of flavour and the sensory test by descriptive ofviscosity. It was concluded that the best quality of fermented milk was BN4 treatment (red dragon fruit extract8%), which meet the quality of fermented milk with a pH of 5.32, total lactic acid 0.92%, total lactic acidbacteria 12.49 log CFU/ml, protein 5.10%, solid total 85.69%, and assessed that panelists preferred thequality attributes of color, taste, flavour and viscosity.